2016
DOI: 10.1111/ases.12286
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative factors predicting the need for additional ports during single‐incision laparoscopic cholecystectomy

Abstract: Our results suggest that gender, prior history of upper abdominal surgery, and white blood cell count can predict the likelihood of requiring an additional port in SILC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Therefore, CLC may be preferred over SILC or additional port insertion may be inevitable during SILC. Sato N. et al argued that the factors that may require additional port insertion during SILC were gender, prior history of upper abdominal surgery, and white blood cell count 20…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CLC may be preferred over SILC or additional port insertion may be inevitable during SILC. Sato N. et al argued that the factors that may require additional port insertion during SILC were gender, prior history of upper abdominal surgery, and white blood cell count 20…”
Section: Discussionmentioning
confidence: 99%
“…Joseph et al [17] reported that SILC-associated bile duct injury occurred in 0.72% of cases during early period; this rate was higher than that compared to the standard LC (0.4%−0.5% of cases). Thus, patient selections are crucial, and risk factors for conversion have been studied [18,19]. Lee and Kim [20] reported a postoperative bile leakage rate of 3.8%, which is higher than that reported in other studies.…”
Section: Discussionmentioning
confidence: 97%
“…El puerto adicional se insertó en el hemi abdomen derecho para no interferir con los otros trocares y fue utilizado para controlar el sangrado por succión o compresión y para mantener una buena visión quirúrgica. (Fujinaga et al, 2022); (Sato et al, 2016).…”
Section: Otras Opciones Descritas Sonunclassified